Back Calculation of Excessive Deformation on Deep Excavation. (2017) - Ma'ruf, M.F.; Darjanto, H.
Abstract: Excessive lateral deformation occurred during the excavation construction exceeded the design criteria. Scrutiny evaluation should be employed to investigate the factor triggering the problems. The evaluation was conducted using numerical analysis by means of PLAXIS 2D 2011. Back calculation modeling results showed that soil investigation did not capture the field condition properly. The existence of small pound and stream next to the field was not taken into account due to the distance of borehole location. Structural work was proposed to overcome the excessive lateral deformation.